ОВЧЕПОЛСКИОТ И СЛОВЕНЕЧКОГОРИШКИОТ (ГОРИЧАНСКИ) ДИЈАЛЕКТ  ДВЕ ПАРАЛЕЛИ ВО ЈУЖНОСЛОВЕНСКИОТ ЈАЗИЧЕН СВЕТ (Philological Studies, 2019)
The aim of this paper is to present parallels between a northeastern Macedonian dialect (Ovche Pole dialect) and a northeastern Slovenian dialect (Slovenian-gorishki – gorichanski dialect). In this respect we will focus primarily on the changes that occur on phonetic-phonological, morphological, lexical and wordformation level in the Ovche Pole dialect, i.e. the language of Crn and Gugj; and on lexical and word-formation level in the Slovenian-gorishki – gorichanski dialect. The rich dialectological material collected in the field indicates that these two dialects are both related and distinct, even though they belong to the South Slavic linguistic world.
Keywords: northeastern Macedonian dialect (Ovce Pole dialect), northeastern Slovenian dialect (Slovenian-gorishki – gorichanski dialect), north Macedonian dialect, Pannonian dialect, dialectological questionnaire, dialectological cards, phonetic-phonological, morphological, lexical language level and word formation